Optimization of the pressure swing distillation process with an intermediate stream for separation of a azeotropic mixture of Diisopropyl Ether/Isopropyl Alcohol (Research, Society and Development, 2022)
Regarding industrial processes, the need to reduce the high energy demand associated with the distillation process becomes progressively essential. In addition, there is a growing need to work with more compact plants, aiming to reduce installation costs. Diisopropyl ether (DIPE) is a by-product of the production of isopropyl alcohol (IPA) and both components have high added value, especially in the solvent industry, that is, the separation of this binary mixture is economically attractive. This separation requires an unconventional method since it presents the formation of an azeotrope, which has a minimum boiling point. Therefore, the present work aimed to optimize the separation process of this homogeneous binary mixture through pressure-swing distillation with an intermediate connection (PSDIC). In order to achieve our objective, the PSDIC process was simulated using the Aspen Plus® software and the optimization was performed using the Simulated Annealing Algorithm (SAA) method, implemented in a Matlab® toolbox. Nine variables, divided between operational and project ones, were optimized simultaneously in order to obtain an optimized scenario for the PSDIC process in terms of Total Annual Cost (TAC). The configuration with the best TAC showed savings of 4.47% per year and a reduction in the thermal load of the high pressure column by 2.47%, compared to the base configuration. The insertion of the intermediate connection current contributed to the reduction of the TAC for the evaluated process.